AB1094 ARTERIOSCLEROSIS MAY AFFECT PERIAORTIC/PERIARTERIAL LESIONS AND THEIR ANEURYSMAL CHANGES IN PATIENTS WITH IGG4-RELATED PERIAORTITIS/PERIARTERITIS. (June 2019) - Mizushima, Ichiro; Konishi, Masahiro; Sanada, Hajime; Suzuki, Kazuyuki; Takeji, Akari; Hara, Satoshi; Ito, Kiyoaki; Fujii, Hiroshi; Yamada, Kazunori; Kawano, Mitsuhiro
Abstract : Background: IgG4-related periaortitis/periarteritis (IgG4-PA) is a major organ manifestation of IgG4-related disease (IgG4-RD) [1]. In the affected aorta/artery, arteriosclerotic changes are frequently observed [2]. However, the influence of arteriosclerosis on IgG4-PA and aneurysmal changes of the affected lesions has not been well evaluated. Objectives: This study aimed to clarify the relationship of arteriosclerosis with periaortic/periarterial lesions and their aneurysmal changes. Methods: We retrospectively investigated the medical data, including the presence of IgG4-PA at diagnosis, new development of IgG4-PA during the clinical course, arteriosclerotic and aneurysmal changes of the affected lesions, and classic risk factors for arteriosclerosis in 130 patients with IgG4-RD at a single center in Japan. The relationship of arteriosclerosis with the periaortic/periarterial lesions and their aneurysmal changes was statistically analyzed. Results: Of the 130 patients with IgG4-RD, 44 comprising 39 men and 5 women (mean age 67.4 years) were diagnosed with IgG4-PA. The mean follow-up period was 72.8 months, and the mean serum IgG4 level at diagnosis was 851 mg/dL. The proportions of males (88.6% vs. 55.8%, P <0.001), positive smoking history (81.4% vs. 47.6%, P <0.001), and history of malignancy (36.4% vs. 14.0%, P =0.006) were significantly higher in the 44 patients with IgG4-PA than in the 86 without it. Arterial wall calcification and/or mural thrombus in the affected lesions were detected in 86.0% of the IgG4-PA patients, some of whom had had these arteriosclerotic changes before the development of periaortic/periarterial lesions. Of the 44 with IgG4-PA, 9 had aneurysmal changes of the affected lesions at the time of the first diagnosis of IgG4-RD. Notably, these 9 patients with aneurysmal changes had a significantly higher incidence of hypertension (77.8% vs. 34.3%, P =0.027) and mural thrombus in the affected lesions (100% vs. 64.7%, P =0.044) than the remaining 35 without aneurysmal changes. However, diabetes mellitus, dyslipidemia, smoking history, C-reactive protein level elevation, or arterial wall calcification of the affected lesions did not differ significantly between the two groups. Conclusion: The present study suggests that arteriosclerotic changes and the classic risk factors for arteriosclerosis may be related to periaortic/periarterial lesions and their aneurysmal changes in IgG4-PA. References: [1] Stone JH, et al. IgG4-related disease. N Engl J Med. 2012 Feb 9;366(6):539-51. [2] Inoue D, et al. Immunoglobulin G4-related periaortitis and periarteritis: CT findings in 17 patients. Radiology. 2011 Nov;261(2):625-33. Disclosure of Interests: None declared